2012
DOI: 10.1016/j.jval.2011.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Agreement between Internet-Based Self- and Proxy-Reported Health Care Resource Utilization and Administrative Health Care Claims

Abstract: This study's agreement values suggest that Internet-based surveys are an effective method to collect self- and proxy-reported HCRU data. These results should increase confidence in the use of the Internet for evaluating disease burden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 33 publications
3
17
0
Order By: Relevance
“…Our results are consistent with previous studies of the accuracy of parental reports of health care resource utilization for paediatric patient populations . Taken together, they suggest that parental surveys can be a useful data collection tool for generating health care resource utilization estimates in evaluations of paediatric diagnostic GWS services.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our results are consistent with previous studies of the accuracy of parental reports of health care resource utilization for paediatric patient populations . Taken together, they suggest that parental surveys can be a useful data collection tool for generating health care resource utilization estimates in evaluations of paediatric diagnostic GWS services.…”
Section: Discussionsupporting
confidence: 91%
“…Agreement for hospitalizations was high, with ratings for only 5 of 89 cases disagreeing. Despite the low prevalence of hospital admissions, categorical measures of agreement indicated “substantial” or “almost perfect” agreement (κ = 0.71, 95% CI: 0.50‐0.91; PABAK = 0.89, 0.75‐0.96), which is comparable or better than the kappa scores reported for hospitalizations in other studies of paediatric patients (eg, 0.53, 0.55, 0.57, and 0.80). Moreover, the agreement in the frequency of hospitalizations was “excellent” (ICC = 0.77, 0.66‐0.84) and much higher than that reported in a study of the general patient population (ICC = 0.14, 0.11‐0.17) …”
Section: Resultssupporting
confidence: 46%
See 1 more Smart Citation
“…With regard to health care use, a dichotomous measure was used as several studies based on comparisons with registered data have indicated that measures of any medical use (0–1) were more accurate than measures of the quantity of use [54-56]. Respondents who had contacted a GP, psychiatrist, or psychologist because of social or emotional problems in the year before the interview were given a score of 1 (16.4%) on professional health care use.…”
Section: Methodsmentioning
confidence: 99%
“…A dichotomous measure was used as several studies based on comparisons of survey data with registered data have indicated that measures of any medical use (0-1) were more accurate than measures of the quantity of use (Palmer et al, 2012;Ritter et al, 2001). …”
Section: Mental Health Care Usementioning
confidence: 99%